What makes Xanthomonas albilineans unique amongst xanthomonads? - Pieretti, Isabelle; Pesic, Alexander; Petras, Daniel; Royer, Monique; Süssmuth, Roderich D.; Cociancich, Stéphane (Frontiers in Plant Science, 2015)
Xanthomonas albilineans causes leaf scald, a lethal disease of sugarcane. Compared to other species of Xanthomonas, X. albilineans exhibits distinctive pathogenic mechanisms, ecology and taxonomy. Its genome, which has experienced significant erosion, has unique genomic features. It lacks two loci required for pathogenicity in other plant pathogenic species of Xanthomonas: the xanthan gum biosynthesis and the Hrp-T3SS (hypersensitive response and pathogenicity-type three secretion system) gene clusters. Instead, X. albilineans harbours in its genome an SPI-1 (Salmonella pathogenicity island-1) T3SS gene cluster usually found in animal pathogens. X. albilineans produces a potent DNA gyrase inhibitor called albicidin, which blocks chloroplast differentiation, resulting in the characteristic white foliar stripe symptoms. The antibacterial activity of albicidin also confers on X. albilineans a competitive advantage against rival bacteria during sugarcane colonization. Recent chemical studies have uncovered the unique structure of albicidin and allowed us to partially elucidate its fascinating biosynthesis apparatus, which involves an enigmatic hybrid PKS/NRPS (polyketide synthase/non-ribosomal peptide synthetase) machinery.